Савромат-Cармат тайпаларының шығу тарихы (Journal of history-rus, 2023)
The warlike nomads, skilled equestrians, well-aimed archers and courageous warriors who inhabited the Eurasian continent in the first millennium BC known in history as the “nomadic tribes of horsemen”. Based on historical data Sauromates-Sarmatian tribes occupy a special place in history. The historical evidence suggests that these tribes lived on a large territory in the east from the southern Ural Mountains, in the west to the Danube River. Due to the migration of these tribes to the west, in written sources before the IV century BC is  frequently occur the name “Sauromate”, and in written sources after the IV century BC – the name “Sarmata”. Moreover, in the oldest religious book of the Iranians the “Avesta” these tribes known as “Sarima”. Now among scientists and researchers the issues of the Sauromat-Sarmatian tribes’ origin, the territory of their land and their political history are still one of the problems that have not found a common solution. For these reasons, this article examines the history of origin, inhabited territories and the political history of the Sauromat-Sarmatian tribes, and draws scientific conclusions based on written sources and archaeological data. In addition, the article analyzed and established a connection with political history based on written data on the campaigns of these tribes to the West.